2018
DOI: 10.1016/j.biomaterials.2018.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Poly(propylacrylic acid)-peptide nanoplexes as a platform for enhancing the immunogenicity of neoantigen cancer vaccines

Abstract: Cancer vaccines targeting patient-specific tumor neoantigens have recently emerged as a promising component of the rapidly expanding immunotherapeutic armamentarium. However, neoantigenic peptides typically elicit weak CD8 T cell responses, and so there is a need for universally applicable vaccine delivery strategies to enhance the immunogenicity of these peptides. Ideally, such vaccines could also be rapidly fabricated using chemically synthesized peptide antigens customized to an individual patient. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
94
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 61 publications
(74 reference statements)
3
94
0
2
Order By: Relevance
“…[134] When the antigen-loaded micelles entered endosomal compartments, the acid environment protonated the carboxylate residues of PAA and increased the positive charge in DMAEMA residues. [133] The polyPAA/peptide nanoplexes showed extended retention in DC2.4 cells and enhanced presentation on MHCI. [134,186] The authors found that a majority of OVA delivered by pH-responsive micelles was able to retain within DC cells in vitro for nearly 1.5 h, while non-pH-responsive micelles showed more than 60% antigen exocytosis in 15 min.…”
Section: Doi: 101002/advs201900101mentioning
confidence: 95%
See 2 more Smart Citations
“…[134] When the antigen-loaded micelles entered endosomal compartments, the acid environment protonated the carboxylate residues of PAA and increased the positive charge in DMAEMA residues. [133] The polyPAA/peptide nanoplexes showed extended retention in DC2.4 cells and enhanced presentation on MHCI. [134,186] The authors found that a majority of OVA delivered by pH-responsive micelles was able to retain within DC cells in vitro for nearly 1.5 h, while non-pH-responsive micelles showed more than 60% antigen exocytosis in 15 min.…”
Section: Doi: 101002/advs201900101mentioning
confidence: 95%
“…[130,131] These clinical researches confirmed their great therapeutic potential as antitumor agents. [56,126,[132][133][134] In this section, we overview the recent developments in the use of engineered nanoparticles to enhance cancer immunotherapy. [67] To achieve precise and controlled drug delivery, smart nanoparticles with more complex structures and specific drug release properties are also being produced according to the hallmarks of TME, such as weak acidic pH (6.5-6.8), high level of glutathione and hydrogen peroxide (H 2 O 2 ), and disorder of proteinases production, such as matrix metalloproteinase-2 (MMP-2).…”
Section: Doi: 101002/advs201900101mentioning
confidence: 99%
See 1 more Smart Citation
“…Antigen release profile was modulated by exploiting endosomal escape mechanisms and enhancing delivery of antigenic cargo to the cytosol for processing, which induces enhanced and sustained MHC class I presentation of peptide antigen by DCs . Qiu et al have developed polyplex nanoparticles (nanoplexes) via simple mixing of decalysine‐modified antigenic peptides and poly(propylacrylic acid) (pPAA), a linear amphiphilic polyanion with a p K a value of 6.7 as a cytosolic antigen delivery carrier which has pH‐dependent membrane destabilizing activity ( Figure A) . To prepare electrostatically stabilized complexation between the peptide antigen and pPAA, peptides containing the mouse MHC class I (H‐2K b )‐restricted epitope, SIINFEKL, from ovalbumin (OVA) as a model antigen were modified with a cationic N‐terminal decalysine (K 10 ) tail (K 10 OVA).…”
Section: Application Of Polymeric Nanomedicine To Cancer Immunotherapymentioning
confidence: 99%
“…F) B3Z T cell response after DC were treated with each formulation for 4 h at 10 × 10 −6 m peptide, followed by coculture with B3Z hybridoma T cells for 24 h. G) B3Z T cell response to DC2.4 cells at different peptide concentrations. Reproduced with permission . Copyright 2018, Elsevier.…”
Section: Application Of Polymeric Nanomedicine To Cancer Immunotherapymentioning
confidence: 99%